2001
DOI: 10.1016/s0014-5793(01)03227-6
|View full text |Cite
|
Sign up to set email alerts
|

NGF‐dependent and tissue‐specific transcription of vgf is regulated by a CREB–p300 and bHLH factor interaction

Abstract: Neurotrophins support neuronal survival, development, and plasticity through processes requiring gene expression. We studied how vgf target gene transcription is mediated by a critical promoter region containing E-box, CCAAT and cAMP response element (CRE) sites. The p300 acetylase was present in two distinct protein complexes bound to this region. One complex, containing HEB (ubiquitous basic helix^loop^helix (bHLH)), bound the promoter in non-neuronal cells and was involved in repressing vgf expression. Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Nonetheless, NGF has minimal ability to activate CREB-mediated gene transcription (52)(53)(54) as well as P2X 3 gene expression in TG neurons (22). In the present investigation, BDNF was an intermediate of the CGRP-induced events and was, per se, an adequate stimulus for P2X 3 gene transcription in TG neurons as much as CGRP itself.…”
Section: Molecular Elements Involved In P2x 3 Gene Transcriptionmentioning
confidence: 44%
“…Nonetheless, NGF has minimal ability to activate CREB-mediated gene transcription (52)(53)(54) as well as P2X 3 gene expression in TG neurons (22). In the present investigation, BDNF was an intermediate of the CGRP-induced events and was, per se, an adequate stimulus for P2X 3 gene transcription in TG neurons as much as CGRP itself.…”
Section: Molecular Elements Involved In P2x 3 Gene Transcriptionmentioning
confidence: 44%
“…A number of studies have demonstrated that HEB is able to function both as an activator and a repressor on a given promoter, depending on the presence of other factors (31,45,54). In particular, HEB represses activation of the GAP-43 gene in PC12 cells, pending expression of Nex1/MATH2, a member of the neuroD family of bHLH factors (50).…”
Section: Discussionmentioning
confidence: 99%
“…The promoter regions of some other genes were shown to possess juxtaposed or overlapping CRE and E box elements. The cooperativity between their respective binding factors could be either positive, as for the follicle-stimulating hormone-mediated activation of the transferrin promoter (16) or for the mouse renin promoter (67), negative, as for the cholecystokinin gene promoter (70) or for the macrophage cyclooxygenase-2 promoter (60), or context dependent, as for the vgf gene promoter (53). In the BLV promoter, the CRE consensus within the three TxREs is never strictly conserved in any viral strain.…”
Section: Discussionmentioning
confidence: 99%